SOFTWARE MARKETING PRODUCTS, FACTORY AND WEB-BASED TEA PROCESSING MACHINE AT CV PRIMA PUTRA BANDUNG - NINA AMALIA (INFOKOM (Informatika & Komputer), 2018)
Marketing is an integrated communication process that aims to provide information about goods or services in relation to satisfying human needs and wants. As a company engaged in the field of Industrial Engineering and machinery, CV. Prima Putra in particular the sales department has a problem to market its products, especially to market products to areas outside the city of Bandung. So it takes a good marketing strategy that can attract and reach more consumers and also can meet the needs of consumers. To handle the problem, then created a web-based product marketing software. The methodology used in this research is Object-oriented method or OOP (Object Oriented Program) using the design tools such as: Usecase, Activity Diagram, and others. While in the development of the software using CMS (Content Management System) in this case CMS used is CMS Joomla and for its database using MySql. So with the manufacture of marketing software product factory and tea processing machine based web can help the sales to make it easier in doing marketing activities.